The sugary added food and beverages consumption and its association with the nutritional status of children age 10-11 years old in Kota Bharu, Kelantan - Mahmood, Wan Noor Najihah Wan (2017)
This study aims to determine the association between the sugary added food and beverages consumption with the nutritional status (BMI-for-age and height-for-age) among children age 10-11 years old. A total of 180 children aged 10- 11 years old attending primary school in Kota Bharu were included in this cross-sectional study. The food intake was assessed by using Food Frequency Questionnaire (FFQ). Anthropometric measurements were conducted in order to calculate the BMI of the children and the sociodemographic questionnaires were answered by parents. The sociodemographic profile showed most of the parents were employed and the highest prevalence of educational level was secondary school. More than half (50.5%) of the students came from the family with the household size between 6-8 people. Most of the household were in the category of which had salary more than RM3500 per month. Most of the household were in the category of which spending more than RM750 per month on food. According to food frequency score, most of the food and drinks were consumed moderately (30.0- 79.9 score) and only ice cream was in the category of mostly consumed food (80.0-100.0 score). More than half (55.6%) of the children had normal BMI, followed by thinnest (12.8%), overweight and obese (12.2% respectively) and severe thinnest (7.2%). Besides,most (82.8%) of the students also have normal height-for-age while 14.4% and 2.8% of them were stunted and severely stunted. The only food items associated with the nutritional status (BMI-for-age) was “sirap drink” (χ2 = 6.119, p = 0.045). No association between sugary added food and beverages consumption with height-for-age was found. There is a significant relationship between sugary added food and beverages consumption of “air sirap” and nutritional status (BMI-for-age).